2013
DOI: 10.1007/s10661-013-3447-1
|View full text |Cite
|
Sign up to set email alerts
|

Relations between macroinvertebrates, nutrients, and water quality criteria in wadeable streams of Maryland, USA

Abstract: In an ongoing effort to propose biologically protective nutrient criteria, we examined how total nitrogen (TN) and its forms were associated with macroinvertebrate communities in wadeable streams of Maryland. Taxonomic and functional metrics of an index of biological integrity (IBI) were significantly associated with multiple nutrient measures; however, the highest correlations with nutrients were for ammonia-N and nitrite-N and among macroinvertebrate measures were for Beck's Biotic Index and its metrics. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…x is consistent with the literature, as it has been shown that there is a strong relationship between nutrient concentrations and macroinvertebrate communities (Ashton et al, 2014).…”
Section: Nhsupporting
confidence: 92%
“…x is consistent with the literature, as it has been shown that there is a strong relationship between nutrient concentrations and macroinvertebrate communities (Ashton et al, 2014).…”
Section: Nhsupporting
confidence: 92%
“…When the focus is on differences in average nitrogen levels among watersheds driven by different amounts of nitrogen enrichment, frequent sampling may not be needed. Our results also support stream assessment protocols that collect one spring nitrate sample to assess watershed and stream nitrogen status (Ashton et al 2014, Stranko et al 2017).…”
Section: Discussionsupporting
confidence: 84%
“…For each site, we selected from the CBNTN concentration database the first uncensored TN and NO 3 measurements taken in March 2012 (see Moyer et al [2012] for information on censoring). The month of March begins the period when streams are commonly visited for stream assessment (e.g., Ashton et al 2014, Stranko et al 2017). We call these potential predictors fsTN and fsNO 3 in the rest of the paper.…”
Section: Methodsmentioning
confidence: 99%
“…Although nutrient pollution is part of the human disturbance gradient, studies investigating the link between macroinvertebrate responses and nutrients vary and, at times, conflict in their results (Calhoun, Gregory, & Weyers, 2008; Wang, Robertson, & Garrison, 2007). Although macroinvertebrates exhibit decreasing trends with increasing nutrient concentrations, relationships are often inconsistent and confounded by co‐occurring factors related to instream habitat, hydromorphology, riparian condition, and surrounding land use (Ashton, Morgan, & Stranko, 2014; Genito, Gburek, & Sharpley, 2002; Kyriakeas & Watzin, 2006; Miltner & Rankin, 1998; Wang et al., 2007; Yuan & Norton, 2004).…”
Section: Introductionmentioning
confidence: 99%